Problems and prospects of catering in glamping - Maksimova, V. I.; Fomina, A. A. (Russian State University of Tourism and Service (RSUTS), 2023)
The article discusses the problems and prospects of catering in such alternative accommodation facilities as glamping. The characteristic of alternative accommodation facilities operating on the territory of the Russian Federation and in the Republic of Karelia is given. Advantages and prospects of glamping development are determined. Problems in the organization of high-quality food in glamping are revealed. The requirements that apply to catering units with any accommodation facility are disclosed. Recommendations are given on the proper organization of nutrition, in compliance with sanitary and preventive measures, including the organization of the technological process, forms of service, methods of catering, considering the needs of consumers, options for improving quality nutrition in glamping.